Early recurrence or submucosal residual of laryngeal squamous cell carcinoma: Diagnosis by CT‐guided endolaryngeal core biopsy on a transcutaneous approach. Issue 7 (22nd May 2012) - Rousset, Jean; Abgral, Ronan; Chinellato, Sandra; Garetier, Marc; Barberot, Céline; Valette, Gérald; Potard, Gaël; Le Bivic, Thierry; Salaun, Pierre–Yves; Chen, Amy
Abstract Background Ultrasound and CT‐guided biopsy is a common procedure for histologic diagnosis of recurrence of head and neck squamous cell carcinoma. The present study describes a novel CT‐guided endolaryngeal puncture site. Methods and Results A 59‐year‐old man was treated for a T2N0M0 supraglottic laryngeal tumor by laser resection and bilateral lymph node dissection; exeresis was judged complete. Six‐month follow‐up found persistent dysphonia. Endoscopic examination and iterative biopsy gave reassuring results, but 18fluorodeoxyglucose positron emission tomography‐CT (18FDG PET‐CT) found highly suspicious increased right hemilaryngeal metabolic activity. Diagnosis of residual tumor was confirmed on CT‐guided endolaryngeal biopsy. Conclusions Image‐guided biopsy is the technique of choice in head and neck lesions that are deep or difficult to palpate and inaccessible to endoscopy. It is especially useful when recurrence is suspected after radiation therapy or cancer surgery. Many puncture sites have been reported in the literature; the present novel laryngeal approach extends the range of image‐guided biopsy, although further studies will be needed to assess possible morbidity. © 2012 Wiley Periodicals, Inc. Head Neck, 2013